Análise experimental de um trocador de calor por mudança de fase e desenvolvimento de um modelo numérico simplificado - Obata, Daniel Henrique de Sousa [UNESP] (2014)
This paper presents the study and one simplified modeling of a compact heat exchanger by phase change for electronic equipment, by experimental techniques and numerical simulations. This exchanger with very efficient characteristics of scattering heat, begins to be increasingly used in the electronics industry, since the electronics are becoming smaller and with high heat dissipation. This makes the thermal design and numerical simulations be increasingly important in the development of electronic equipment and come supply the scarcity of the exchanger models which are easily applicable in commercial software. In this paper we also will analyze the behavior of the exchanger in the using of the heat source in various positions not only in the central region where the heat source is usually located in the literature